Academies and Educational Reform : Governance, Leadership and Strategy - Leo, Elizabeth ; Galloway, David, and Hearne, Phil (Bristol Multilingual Matters, 2010)
Academies were developed to replace schools struggling to educate children and young people living in disadvantaged communities. This book considers what has distinguished academies from other secondary schools and whether academies can legitimately be seen as an effective way to achieve sustained improvement in state schools.
Include Index and Illustration
Keywords: Youth with social disabilities--Education (Secondary) -- Great Britain -- Academies (British public schools)